2019
DOI: 10.3390/sym11091094
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of Chiral Schiff Base Metal Complexes Involving Azo-Groups for Induced CD on Gold Nanoparticles by Polarized UV Light Irradiation

Abstract: In this study, we report the synthesis, characterization, and chiroptical properties of azo-group-containing chiral salen type Schiff base Ni(II), Cu(II), and Zn(II) complexes absorbed on gold nanoparticles (AuNPs) of 10 nm diameters. Induced circular dichroism (CD) around the plasmon region from the chiral species weakly adsorbed on the surface of AuNP were observed when there were appropriate dipole–dipole interactions at the initial states. Spectral changes were also observed by not only cis-trans photoisom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Since the salen-type ligand is considered to have a weak crystal field, the calculation was performed assuming a d 9 for Cu(II) and high spin d 4 for Mn(III). The calculation strategy was based on previous studies of Schiff base complexes [ 20 , 21 ]. Density functional theory (DFT) was used together with B3LYP functional for all calculations because of the balance between calculation accuracy and calculation time.…”
Section: Methodsmentioning
confidence: 99%
“…Since the salen-type ligand is considered to have a weak crystal field, the calculation was performed assuming a d 9 for Cu(II) and high spin d 4 for Mn(III). The calculation strategy was based on previous studies of Schiff base complexes [ 20 , 21 ]. Density functional theory (DFT) was used together with B3LYP functional for all calculations because of the balance between calculation accuracy and calculation time.…”
Section: Methodsmentioning
confidence: 99%
“…Manganese(II) chloride tetrahydrate, zinc(II) acetate dihydrate, aniline, sodium nitrite and sodium hydroxide were purchased from Kanto Chemical Co., Inc. Salicylaldehyde, p-anisidine and 4-aminobenzoic acid were obtained from Tokyo Chemical Industry. [5]. AgNPs (30 -80 nm) were synthesized using a modified polyol method [6] [7].…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, we have carried out photochemical studies on chiral azo-Schiff base metal complexes as hybrid materials, for example, focusing on (with titanium oxide) cis-trans photoisomerization of azobenzene moiety [1], non-linear optical effect of chiral molecules [2], (with gold nanoparticles) induced circular dichroism (CD) as supramolecular chiroptical measurements of chiral molecules [3] [4] and polarized light control of molecular orientation on the surface resulted from induced CD due to Weigert effect of azobenzene moiety [5]. In this way, we attempted new mechanisms to improve the performance of DSSC in future.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the adsorption of a chiral substance on an achiral medium or reverse may affect the spectrum of a circular dichroism (CD) of such composites causing an interesting phenomenon of induced circular dichroism (ICD) [ 50 , 51 , 52 , 53 ]. Tsutsumi et al [ 54 , 55 , 56 , 57 , 58 ] observed such effects in hybrid systems of Schiff base metal complexes deposited on nano-inorganic substances (namely metal nanoparticles or semiconductor nanoparticles). They studied the influence of bromination on the molecular dipole moment and the CD behavior.…”
Section: Ligand-induced Chirality In Chiral Schiff Base Complex @ Nan...mentioning
confidence: 99%